Ingham of Arabia : a collection of articles presented as a tribute to the career of Bruce Ingham - Holes, Clive, 1948-; Jong, Rudolf Erik de; Ingham, Bruce (Studies in Semitic languages and linguistics ;, 2013)
Ingham of Arabia is a collection of twelve articles on modern Arabic dialectology, covering Oman, Jordan, Sinai, the Negev, southern Turkey, Syria; and other articles concerning general topics in Arabic dialectology.